As representações de desejo e prazer sadomasoquistas em Leopold Von Sacher-Masoch e Wilma Azevedo - Germano, Iara Ferreira (2023)
This present work analyzes the representations of sadomasochistic (SM) desires and pleasures in the Austrian novel “Venus in Furs” (1870) by Leopold von Sacher-Masoch, and in the short story collections “A Vênus de Cetim” (1986) and “Tormentos Deliciosos” (1995) by Brazilian writer Wilma Azevedo. The analyzed works are erotic texts that portray erotic practices in which characters are aroused by submission or domination, receiving, or causing pain, tying, or being tied up, and so on. Based on these representations, our objectives are to analyze the representation of SM desires and pleasures in order to propose an interpretation that distances SM erotic practices from hegemonic pathologizing and criminalizing discourses; to compare Sacher-Masoch’s novel with Azevedo's two short story collections in order to perceive possible connections between the texts; and to propose a formal analysis of the erotic text, considering the elements that characterize them as such and are capable of producing an obscene effect on the reader (FRAPPIER-MAZUR, 1999; GOULEMOT, 2000). We conclude that sadomasochistic erotic literature inspires, challenges, and opens up new paths to explore and understand the multiple possibilities of sexual practices, since just like in literary creation, the limits of sadomasochistic practices are the limits of the imagination. It was also possible to conclude that there is a relationship of intertextuality between Sacher- Masoch’s work and Wilma Azevedo’s. As for the formal analysis of the text, we conclude that the obscene effect is produced in the reader through the use of obscene language. However, the response produced depends on the idiosyncrasies of the reader, as it is necessary for the text to resonate with their imagination and fantasy.